Different imazethapyr placements and rainfall amounts affect phytotoxic activity of imazethapyr in combination with oil palm frond residue mulches against common weeds in landscapes - Muhammad Amirul Nordin,; Dilipkumar Masilamany,; Chuah, Tse Seng (Penerbit Universiti Kebangsaan Malaysia, 2019)
A combination of oil palm frond (OPF) mulch and imazathapyr has been shown to provide great inhibition of weed but its phytotoxicity may be influenced by imazethapyr placement on the OPF mulch and rainfall amount. This study aimed to evaluate effects of herbicide placement and rainfall amount on the phytotoxic activity of imazethapyr in combination with OPF mulches against goosegrass, slender cyperus and coat buttons under glasshouse conditions. Imazethapyr was applied at 10.4 g a.i. ha-1 to under or above or as a pretreatment on the OPF mulch residue powder (< 2 mm) at 3.5 t ha-1. Imazethapyr placement did not influence its inhibitory effects against weed emergence. Both pretreated mulches and imazethapyr applied under the mulches had comparable inhibition of seedling growth for goosegrass and slender cyperus. However, the pretreated mulches gave better seedling growth inhibition of both bioassay species as compared to those of imazethapyr that applied above mulches. Coat button was highly inhibited regardless of any imazethapyr placements. An increase in rainfall amount from 150 to 450 mm could increase the seedling emergence of goosegrass and slender cyperus from 30 to 80% when subjected to pretreated mulches. However, different rainfall amounts had no significant effect on coat buttons seedling emergence. The pretreated mulches could reduce weed seedling growth by 75 to 80% without being affected by the rainfall amounts. The present results suggested that phytotoxic activity of imazethapyr in combination with OPF residue mulches is dependent on imazethapyr placement, rainfall amount and weed species.